Pengaruh Brand Satisfaction, Brand Trust, dan Brand Experience Terhadap Brand Loyalty Kompas Digital - Ignatius Aditya dan Miharni Tjokrosaputro (Universitas Tarumanagara, 2020)
This research was conducted in order to assess the effect of brand satisfaction, brand trust, and brand experience to brand loyalty of Kompas digital. The research implemented quantitative method, in which questionnaire were distributed to a total of 150 respondents, thus enabling the data to be analyzed. Data were collected from respondents in Jakarta regions. Data were analyzed by SPSS version 21.00 for windows using multiple linier regression method. After conducting data analysis, it was revealed that brand satisfaction and brand experience individually have a positive impact on brand loyalty. Meanwhile brand trust doesn’t have a positive impact toward brand loyalty. But all three variables simultaneously have a significant effect toward brand loyalty.